Strength of Proof of Deeds Stored Digitally - Zainuddin*, Zainuddin; Ikhsan, Dadang Fathul (Universitas Syiah Kuala, 2023)
Implicitly, the deposit of the minutes of the deed is contained in Article 16 paragraph (1) letter g of the Notary Position Act, which states that the Notary must bind the deed every month. However, the effectiveness of manual storage must be reviewed because it is at risk of fire, natural disasters, is not cost-effective, does not save space, and makes it difficult for Notaries to re-find old deeds that they have made if necessary. Digital storage is a new solution, however, regarding the rules for digitally storing minutes, there is no legal vacuum and the legal certainty is questioned, coupled with Article 5 paragraph (4) letter b of the Electronic Information and Transaction Law which is indicated to make digital storage difficult and making the proof of minutes stored digitally weak. The purpose of this study is to find out about the form of storing minutes of deeds that are stored digitally and to know the strength of proof of minutes of deeds that are stored digitally. This legal research is a normative legal research. The approach in this research is a statutory approach and a conceptual approach. The form of digital Minuta Deed storage is by using sheet scanning on the Minuta Deed, then storing it in a secondary storage device and can also save it using a storage service. In general, the strength of proof of the Minutes of Deed that is stored manually is the power of proof that is perfect and binding. Meanwhile, the minutes that are stored digitally have the power of proof such as an underhand deed. So that the storage of the Minutes of Deed digitally only functions as back up data, does not have the same evidentiary power as the Minutes of Deed and Copies of the deed, because digital documents in the notarial field are not recognized as legal evidence in Article 5 paragraph (4) letter b of the Law. Law on Information and Electronic Transactions